Peran Notaris Dalam Melindungi Status Hak Milik Atas Tanah Akibat Perkawinan Campuran - Mulyani, I Gusti Agung dewi; Wiryawan, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020)DO - 10.24843/AC.2020.v05.i03.p12, 2020)
In the ruling man is created unable to live alone, the law is human created to live both and add to his descendants and successors. This leads to a bond of marriage between men and women, whose purpose is to create happy families and homes, harmoniously with the virtue of the one true deity. The marriage is held with the Customs and culture of each party, because basically the two human beings are backed by different customs and cultures. Indonesia's state with a forward minded society wants to make its life more improved, both in the field of work and home, not infrequently in the Indonesian economic system has established relationships with foreign nationals as Investors to improve the economic system in Indonesia. It is not uncommon for Indonesian citizen to have a relationship with foreigners to work, do business, and be friends and friendly, because humans are created to require each other, profitable, and adjoining. The relationship between WNI and WNI is not uncommon in marital relationship, namely mixed marriage between citizens and foreigners who occur on the basis of affection and love and want to live a life together. The marriage itself has been governed in the marriage act , i.e. the marriage has been recognized by the State, and against the marriage of the mix has also been recognized by the state because it has been demonstrated and regulated in the marriage act as well. Through life, in it for future survival, sought and acquired wealth that can be a common treasure or can also be a split. The common treasures are the treasures obtained throughout the marriage, without the agreement of marriage. The Covenant of marriage is made with the purpose of the separation of the property of each party, meaning there is no mixing of possessions in the family, and with this each party has each responsibility. In this journal is conducted empirical research because it is to be able to discuss issues raised as to how the role of notary in protecting the status of property rights on land resulting from mixed marriages and how the status of ownership On the ground when a divorce occurs, it must be research directly with the source of space. Implemented using the fact approach, and the collection of secondary data and primary data, so as to discuss the role of notary in protecting the property rights on land is to make a marriage agreement before or after the marriage In progress, by providing legal certainty against the separation of the property that has occurred and the status of ownership of the land when divorce occurs can remain the property of Indonesian citizens, or the status is given to children born of marriage The